Investigation of the electronic and thermoelectric properties of nitrogen chains doping SWCNT: ab initio study - Takassa, Rabi; El Mouncharih, Abdelkarim; Farkad, Omar; Elfatouaki, Fatima; Hassine, Sanae; Ouahdani, Abdellatif; Ibnouelghazi, El Alami; Abouelaoualim, Driss (European physical journal. Applied physics, 2023)
In this work, we have investigated the electronic and thermoelectric properties of CN, C 2 N 2 and C 4 N 2 nanotubes resulting from doping of nitrogen atoms, three and two N-zigzag chains on small (3,3) single walled carbon nanotube (SWCNT) respectivelly. All calculations were performed via DFT theory using WIEN2K code. The electronic structure calculations were done using GGA with TB-mBJ exchange potential, while the thermoelectric calculations were done using semi-classical Boltzmann transport theory. The results show that all structures are energetically stable. The electronic behaviour of (3,3) SWCNT transforms from semiconductor to metal in CN nanotube and to topological Weyl semimetal (WSM) state for C 2 N 2 and C 4 N 2 nanotubes. The calculations of thermoelectric properties, including electrical conductivity, Seebeck coefficient and power factor, reaveal that the N-doping enhances the thermoelectric properties of pristine nanotube. SWCNT with nitrogen doping has promising electronic and thermoelectric capabilities that make it a potential for electronic and thermoelectric devices.